IoT and analytics in renewable energy systems (volume 2) AI, ML and IoT deployment in sustainable smart cities - Swathika, O. V. Gnana ca. 20./21. Jh; Karthikeyan, K.; Sanjeevikumar, Padmanaban 1978- (CRC Press, 2024)
Volume 2 speaks about Smart cities that emanate from a smart renewable energy aided power grid. The smart grid technologies offer an array of benefits like reliability, availability, and resiliency. Smart grids phenomenally contribute to facilitate cities reach those sustainability goals over time
Keywords: Electric power systems-Data processing; Internet of things; Renewable energy sources